2018
DOI: 10.1111/gfs.12360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus buchneri isolated from tropical maize silage on fermentation and aerobic stability of maize and sugarcane silages

Abstract: This study was aimed to perform a screening of Lactobacillus buchneri strains from maize silage and use them as inoculant in maize and sugarcane silages. In all, 151 lactic acid bacteria (LAB) strains were isolated from whole‐plant maize silage, and their identification was based on the sequence analysis of 16S rDNA. In total, 15 strains were categorized to the L. buchneri group and eight of these were selected based on growth rate and fermentation pattern. The selected strains were evaluated on fermentation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 44 publications
2
19
1
9
Order By: Relevance
“…The genera, Lactobacillus, Streptococcus, and Bifidobacterium that can produce lactic acid [33,34], and the genera, Megasphaera, a commonly known lactic acid utilizing genus [35], all showed higher relative abundance levels in the jejunal microbiome of grain-fed cattle. These genera have long been observed to have a higher abundance in high-grain diet rumen, and in animals with rumen acidosis [36,37]. Our study further showed that from the rumen to the jejunum, these higher abundances in grain-fed cattle remained significant to have more senior activities related to lactate.…”
Section: Discussionsupporting
confidence: 61%
“…The genera, Lactobacillus, Streptococcus, and Bifidobacterium that can produce lactic acid [33,34], and the genera, Megasphaera, a commonly known lactic acid utilizing genus [35], all showed higher relative abundance levels in the jejunal microbiome of grain-fed cattle. These genera have long been observed to have a higher abundance in high-grain diet rumen, and in animals with rumen acidosis [36,37]. Our study further showed that from the rumen to the jejunum, these higher abundances in grain-fed cattle remained significant to have more senior activities related to lactate.…”
Section: Discussionsupporting
confidence: 61%
“…Propionic acid (Wang, Yu, Wu, & Hannaway, ) or heterofermentative LAB, such as L . buchneri (Silva et al., ) and L . brevis (Daniel et al., ), are usually used to alleviate this deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the fermentation completed and the silage exposed to air, undesirable microorganisms will use the lactic acid or residue WSC to lead to the nutrient loss and health risks for animals and humans (Tao et al, 2017). Propionic acid (Wang, Yu, Wu, & Hannaway, 2018) or heterofermentative LAB, such as L. buchneri (Silva et al, 2018) and L. brevis (Daniel et al, 2015), are usually used to alleviate this deterioration. Heterofermentative LAB are characterized by the production of acetic acid, which is considered useful for increasing aerobic stability (Tobacco, Piano, Revello, & Borreani, 2011), and propionic acid is an aerobic microbial inhibitor that can effectively inhibit the activity of moulds and yeasts .…”
Section: Introductionmentioning
confidence: 99%
“…Lactate producers, such as Lactobacillus, Streptococcus, and Bi dobacterium [28,29], and Megasphaera, a commonly known genus harboring many lactic acid utilizers [30], all showed higher abundances in grain-fed cattle. These genera have long been observed to be more abundant in high-grain diet and acidic rumen [29,31]. Solibacillus was reported to decrease when diets were shifted to sub-acute ruminal acidosis induction diets, which potentially related to valerate metabolism [32].…”
Section: Discussionmentioning
confidence: 99%